Effects of biochar and organic-inorganic fertilizer on pomelo orchard soil properties, enzymes activities, and microbial community structure - Song, Yang; Zhao, Quan; Guo, Xiuzhu; Ali, Izhar; Li, Fayong; Lin, Shaosheng; Liu, Dongfeng (Frontiers in Microbiology, 2022)
Fertilizer management can influence soil microbes, soil properties, enzymatic activities, abundance and community structure. However, information on the effects of biochar in combination with organic-inorganic fertilizer after three years under pomelo orchard on soil bacterial abundance, soil properties and enzyme activities are not clear. Therefore, we conducted a field experiment with seven treatments, i.e., (1) Ck (control), (2) T1 (2 kg biochar plant-1), (3) T2 (4 kg biochar plant-1), (4) T3 (2 kg organic-inorganic mixed fertilizer plant-1), (5) T4 (4 kg biochar + 1.7 kg organic-inorganic mixed fertilizer plant-1), (6) T5 (4kg biochar + 1.4 kg organic-inorganic mixed fertilizer plant-1), and (7) T6 (4kg biochar + 1.1 kg organic-inorganic mixed fertilizer plant-1). The soil microbial communities were characterized using high-throughput sequencing of 16S and internal transcribed spacer (ITS) ribosomal RNA gene amplicons. The results showed that biochar combined with organic-organic fertilizer significantly improved soil properties (pH, alkali hydrolysable nitrogen, available phosphorus, available potassium and available magnesium) and soil enzymatic activities (urease, dehydrogenase (DHO), invertase and nitrate reductase (NR) activities). Furthermore, soil bacterial relative abundance was higher in biochar and organic-inorganic treatments as compared to control plots and the most abundant phyla were Acidobacteria (40%), Proteobacteria (21%), Chloroflexi (17%), Planctomycetes (8%), Bacteroidetes (4%), Verrucomicrobia (2%) and Gemmatimonadetes (1%) among others. Among the treatments, Acidothermus, Acidibacter, Candidatus Solibacter and FCPS473 bacterial genera were highest in combined treatments of biochar and organic-inorganic appliedbiochar and organic-inorganic treatments. The lowest bacterial abundance and bacterial compositions were recorded in control plots. The correlation analysis showed that soil attributes, including soil enzymes, were positively correlated with Chloroflexi, Planctomycetes, verrucomicrobia, GAL15 and WPS-2 bacterial abundance. This study demonstrated that biochar with organic-inorganic fertilizer improves soil nutrients, enzymatic activities and bacterial abundance.